2012
DOI: 10.1007/s00381-012-1785-x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the management of subependymal giant cell astrocytoma

Abstract: Surgery can be curative; however, not all SEGAs are amenable to safe and complete resection. Gamma Knife stereotactic radiosurgery provides another treatment option but has highly variable response rates with limited data demonstrating its efficacy. Newer medical therapy targeting mammalian target of rapamycin (mTOR), the key protein kinase that is constitutively activated in TSC, has demonstrated promising results in recent clinical trials. In both case reports and clinical trials, treatment with mTOR inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
0
39
0
1
Order By: Relevance
“…Although these lesions are generally benign and noninfiltrative, they can be life-threatening as they arise typically near the foramen of Monro, unilaterally or bilaterally. Serial growth may result in acute or subacute obstructive hydrocephalus [56] and sudden death [57].…”
Section: Neurological Manifestationsmentioning
confidence: 99%
“…Although these lesions are generally benign and noninfiltrative, they can be life-threatening as they arise typically near the foramen of Monro, unilaterally or bilaterally. Serial growth may result in acute or subacute obstructive hydrocephalus [56] and sudden death [57].…”
Section: Neurological Manifestationsmentioning
confidence: 99%
“…SENs positioned in the region of the Monro foramina can grow and transform into a SEGA. It has also been reported that solitary SEGAs even appear in the absence of any other TSC-related lesions [7,18] . Multiple signaling cascades are involved in the focal abnormalities of different organs due to depletion in either of the TSC1/TSC2 gene's second allele.…”
Section: Tsc Manifestation In Gliomagenesismentioning
confidence: 99%
“…The risk factors influencing the genesis of glioma include exposure to toxins such as vinyl chloride, ionizing radiation, electromagnetic radiation, infection with simian virus 40, gene [3] Ependymoma (2%-6% of glioma) [4,5] Astrocytoma (7% of primary brain tumors and 80%-85% of all gliomas) Juvenile pilocytic, pleo morphic and subependymal giant cell astrocytoma (SEGA) [4,[6][7][8][9] Cerebrum (oligodendrocytes) Monomorphous cells with round, regular nuclei with perinuclear halos. Focal calcifications, interspersed delicate capillaries, nuclear labelling for S100 and diffuse background staining for S100 and GFAP are present.…”
Section: Molecular Transformations As Driving Forces In Glial Tumorigmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in incompletely resected SEGAs, up to 100% reoperation rates are noted. 1 Radiosurgery has also been used for inoperable tumors with reported long-term control rates of 67%, 17 and recent introduction of everolimus, an mTOR inhibitor, has provided new options for medical management. 13 Again, there exists a potential role for laser ablation for management of inoperable, symptomatic SEGAs, especially with its potential to reduce tumor volume and improve associated mass effect and/or CSF outlet obstruction.…”
mentioning
confidence: 99%